2022
DOI: 10.1177/21582440221079878
|View full text |Cite
|
Sign up to set email alerts
|

Worry, Perceived Discrimination, Lifestyle Changes, and Protective Factors During COVID-19: A Study With Recovering Patients in Delhi, India

Abstract: COVID-19 has affected people all over the world. For those who were infected by the virus, the repercussions go beyond immediate medical conditions to include social stigma, fear, uncertainty, and lifestyle changes. This study presents data collected as part of a mental health intervention (COVID Response) with individuals who had been diagnosed with coronavirus and had completed the minimum 14 days isolation period, in the city of Delhi, India. Through a survey conducted telephonically, participants self repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 78 publications
1
4
2
Order By: Relevance
“…The number of missing data specifically for this question was particularly high (29% of the sample), suggesting that participants may have been embarrassed to answer questions. Instead, previous research has shown that about 20% of respondents reported discrimination (in U.S. and Indian samples; [ 22 ]) This surprisingly low proportion in the present study is likely due to underreporting, which is quite frequent in the case of personal social rejection [ 55 , 56 ], but also to a lower proportion of ethnic minorities in this database. Indeed, previous studies showed that non-white participants are more likely to report covid-19 discrimination [ 22 , 26 , 28 ], as well as reporting more deleterious consequences on their mental health [ 28 ].…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…The number of missing data specifically for this question was particularly high (29% of the sample), suggesting that participants may have been embarrassed to answer questions. Instead, previous research has shown that about 20% of respondents reported discrimination (in U.S. and Indian samples; [ 22 ]) This surprisingly low proportion in the present study is likely due to underreporting, which is quite frequent in the case of personal social rejection [ 55 , 56 ], but also to a lower proportion of ethnic minorities in this database. Indeed, previous studies showed that non-white participants are more likely to report covid-19 discrimination [ 22 , 26 , 28 ], as well as reporting more deleterious consequences on their mental health [ 28 ].…”
Section: Discussioncontrasting
confidence: 78%
“…The number of missing data specifically for this question was particularly high (29% of the sample), suggesting that participants may have been embarrassed to answer questions. Instead, previous research has shown that about 20% of respondents reported discrimination (in U.S. and Indian samples; [22]) This surprisingly low proportion in the present study is likely due to underreporting, which is quite frequent in the case of personal social rejection [55,56], but also to a lower proportion of ethnic minorities in this database. Indeed, previous studies showed that non-…”
Section: Plos Onecontrasting
confidence: 77%
See 2 more Smart Citations
“…According to Lee et al [ 36 ], it was found that mother’s mental health had more influence on young children’s health prevention behavior than other groups. During the coronavirus pandemic, there have been many studies examining negative mental health factors such as anxiety [ 37 ], psychological instability [ 38 ], harsh parenting [ 39 ], and lack of emotional care [ 40 ] among mothers with young children during the COVID-19 pandemic. Maternal confidence is an important factor that positively influences preventive health behaviors.…”
Section: Discussionmentioning
confidence: 99%